A Feasibility Study on Brand Extension with Reference to Arun (Hatsun Agro Products Ltd.) - Madhavi, C.; Samudhra Rajakumar, C. (Indian Journal of Marketing, 2004)
India is witnessing change in lifestyles of large action Indian population. India is expected to be the second largest market in the world (Hohnot, 1999). The need to understand the emerging markets and consumers has become a big challenge to the corporate world especially in creating and managing a powerful brand. By developing a powerful brand, corporate can establish ’brand equity’ and the equity assist firms in a variety of ways to manage competition and to maintain market share. Now, the Indian market is flooded with plenty of brands both Indian and International. In simple words, a brand is a recognizable and trustworthy badge of origin and also a promise of performance.